2015
DOI: 10.1182/blood-2014-09-600312
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal RNA transfer mediates platelet-induced hepatocyte proliferation

Abstract: Key Points• Platelets stimulate proliferation of HepG2 cells, which requires uptake of platelets by the HepG2 cell.• Platelets stimulate HepG2 cell proliferation in part by transfer of RNA from the anucleate platelet to the nucleated HepG2 cell.Liver regeneration is stimulated by blood platelets, but the molecular mechanisms involved are largely unexplored. Although platelets are anucleate, they do contain coding or regulatory RNAs that can be functional within the platelet or, after transfer, in other cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 39 publications
1
74
1
Order By: Relevance
“…Furthermore, it was reported recently that platelet RNAs are also involved in hepatocyte proliferation processes [26]. While we were able to document the in vivo relevance of 5-HT within the human setting, the relevance of platelet-derived RNAs during liver regeneration in humans remains to be elucidated.…”
Section: How Do Platelets Modulate Liver Regeneration?mentioning
confidence: 67%
“…Furthermore, it was reported recently that platelet RNAs are also involved in hepatocyte proliferation processes [26]. While we were able to document the in vivo relevance of 5-HT within the human setting, the relevance of platelet-derived RNAs during liver regeneration in humans remains to be elucidated.…”
Section: How Do Platelets Modulate Liver Regeneration?mentioning
confidence: 67%
“…Thus, Kirschbaum et al[78] showed that transfer of coding or regulatory RNA could occur between platelets and hepatocytes, promoting hepatocyte proliferation. However, the role of both mechanisms, i.e .…”
Section: Liver Fibrosis and Plateletsmentioning
confidence: 99%
“…Recently, it has been reported that RNA transfer mechanism as an additional contributor to platelet-mediated liver regeneration. 57 The collaborative effect with Kupffer cells. Kupffer cells play a role in the liver as macrophages that act against bacteria, endotoxins, and microbial debris derived from the gastrointestinal tract.…”
Section: 54mentioning
confidence: 99%